2020
DOI: 10.1177/0021998319899129
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal cutting of UD-CFRP using multiscale analysis: Finite element modeling

Abstract: Unsuitable surface quality is frequently observed in the machining of composites due to their heterogeneity and anisotropic properties. Thus, minimizing the machining damages requires a thorough understanding of the machining process. In this study, two different finite element models were developed using Abaqus/Explicit to simulate the cutting process of unidirectional carbon fiber-reinforced polymer: (i) a macromechanical model based on the homogenization approach and (ii) a micromechanical model in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Three main numerical models have been proposed to investigate the cutting process of CFRP, that is, the micro-scale, [9][10][11] macroscale, [12][13][14] and mesoscale finite element model. [15][16][17] And the numerical models have been developed from the twodimensional (2D) to the three-dimensional (3D) at the past decades. These models showed that the principal cutting force predicted fairly acceptable in their model, which agreed with the experimental results, although the thrust force was still not compliant.…”
Section: Introductionmentioning
confidence: 99%
“…Three main numerical models have been proposed to investigate the cutting process of CFRP, that is, the micro-scale, [9][10][11] macroscale, [12][13][14] and mesoscale finite element model. [15][16][17] And the numerical models have been developed from the twodimensional (2D) to the three-dimensional (3D) at the past decades. These models showed that the principal cutting force predicted fairly acceptable in their model, which agreed with the experimental results, although the thrust force was still not compliant.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, crack tip plasticity and creep behaviour of polymers during cutting conditions are completely different in metal materials. In recent years, orthogonal micro-cutting of polymers has drawn increasing attention [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Regarding the numerical method for orthogonal micro-cutting of polymers, Venu Gopala Rao et al [ 19 ] developed an FE model to machine CFRP and GFRP composites.…”
Section: Introductionmentioning
confidence: 99%
“…It was found the ber orientation is the key factor that affects cutting process. With the developing of numerical techniques, simulation models in micro scale [4]-[6], macro scale [7] [8] and multi-scale [9] [10] have been built to study the so called cutting mechanism. Similar results to Wang's work were found that ber orientation controls machined surface roughness, subsurface damage and cutting forces.…”
Section: Introductionmentioning
confidence: 99%